Novel landscape design model system approach: monitoring, predicting and calculating carbon sequestration rate for tourism accommodation premises green spaces - Othman, Rashidi; Abu Kasim, Siti Zubaidah; Hashim, Khairusy Syakirin Has-Yun; Mohd Noor, Nur Fadhlina (Universiti Teknologi Malaysia, 2015)
Carbon emissions is expected to continue to increase unless major changes are made in the way carbon is managed. Managing hotel carbon emissions has emerged as a critical research matter and has become public and national interest since the last century. For instance daily appliances carbon emission from tourism accommodation premises is one of the major contributors for greenhouse effect especially in urban area and this could cause detrimental impact to the surrounding environment. One of the promising approach to reduce carbon emission to the atmosphere is by selecting an appropriate plant materials as well as optimization of spatial and space organization of green spaces. Besides character of the plant materials, criteria such as soil, plant material age, trunk diameter and trunk height are very much influenced the carbon sequestration rate. Therefore this study aimed to develop carbon sequestration model system through landscape design approach that can monitor, calculate and predict the amount of carbon that can be absorbed by proposed plant species at certain period of time. Two existing hotels were selected and the findings of this research showed that at both case studies, carbon sequestration rate by trees has the highest sequestration amount compared to other plant materials. This study also established that even with limited green space areas for tourism accommodation premises such as hotel, the carbon sequestration rate can be further increased with the right selection of plants, at the right place with the right spatial and space organization of green spaces. The significance outcomes of this study will be a novel landscape design approach to neutralize carbon emission which is cost effective and environmental friendly.